High mesothelin expression is associated with low cytotoxic T cell infiltration in pancreatic cancer - Liang, Oliver; White, Amy L.; Fielder, Timothy; Shin, Joo-Shik; Sagnella, Sharon M.; Schmitz, Ulf; Yeo, Dannel (Frontiers in Immunology, 2025)
ObjectivesMesothelin (MSLN) is a cell-surface glycoprotein overexpressed in the majority of pancreatic ductal adenocarcinoma (PDAC) cases and represents a promising immunotherapeutic target. Despite studies and clinical trials investigating MSLN-targeted immunotherapies, its biological role in PDAC carcinogenesis and influence on the tumor microenvironment remain poorly characterized. This study aims to investigate MSLN expression patterns in PDAC and assess their relationship to clinical outcomes and the immune microenvironment.MethodsMSLN expression in 74 PDAC patients was evaluated by immunohistochemistry staining on a tissue microarray and correlated with clinicopathological features and survival outcomes. Complementary analyses of publicly available transcriptomic datasets (bulk RNA-seq and single-cell RNA-seq) were performed to characterize associations between MSLN expression and the tumor immune microenvironment with immunohistochemical validation.ResultsHigh MSLN expression (H-score ≥ 62) was associated with improved relapse-free survival (p = 0.021) and with increased patient age (p = 0.036). Transcriptomic analyses revealed high MSLN expression was associated with an immunosuppressive microenvironment characterized by reduced immune reactivity and diminished cytotoxic T cell infiltration. Immunohistochemical validation confirmed a trend toward decreased stromal cytotoxic T cell abundance with increasing MSLN expression.ConclusionThis study revealed an inverse relationship between MSLN expression and cytotoxic T cell infiltration in PDAC, despite a trend toward improved relapse-free survival in MSLN-high tumors. These findings have important implications for MSLN-targeted immunotherapies and suggest that addressing the immunosuppressive microenvironment may be necessary to optimize their current responses in PDAC.